THE INFLUENCE OF GREEN INTELLECTUAL CAPITAL ON FINANCIAL PERFORMANCE: THE ROLE OF COMPETITIVE ADVANTAGE AS AN INTERVENING VARIABLE - Muhammad Sodri Alamsyah; Windu Mulyasari (ZILLZELL MEDIA PRIMA, 2025)
This study was conducted to examine the influence of Green Intellectual Capital (GIC) which is dimensioned into Green Human Capital (GHC), Green Structural Capital (GSC) and Green Relational Capital (GRC) on financial performance with competitive advantage as an intervening variable. The sample used in this study amounted to 201 data in the 2021-2023 observation year in energy sector companies listed on the Indonesia Stock Exchange as the research population. This study uses a quantitative method with data obtained from the official website of the Indonesia Stock Exchange. The research model uses regression analysis panel data with the best model chosen being the Random Effect Model (REM) and the mediating variable is tested with a sobel test using a sobel test calculator. From the tests carried out, the results of the study show that green human capital and green relational capital have a positive and significant effect on financial performance. Meanwhile, green structuralism has a negative and significant influence on financial performance. The competitive advantage in this study cannot mediate the relationship between green human capital, green structural capital and green relational capital and financial performance.